Do police abuse their powers? - Dudley, William, 1964- (Issues in society (ReferencePoint Press), 2017)
"Police shootings and other questionable acts of misconduct many captured and circulated on video have created a nationwide debate on whether police departments need serious reforms and whether police officers can be trusted. Issues are discussed clearly and objectively, with added insight from experts and others..."--Amazon.com.